Doping is a threat to sporting excellence - Devine, J. W. (British Journal of Sports Medicine, 2011)
Savulescu et al have argued that the risk to athletes' welfare provides the only legitimate ground for restricting the use of performance enhancing drugs in sport. In this paper, it is argued that the idea of `sport', properly understood, provides further reason to impose such restrictions. A `balance of excellences' argument is proposed whereby doping is considered objectionable on account of its disrupting the relation between the excellences around which sporting competition is organised. We have reason to restrict the use of performance enhancing drugs in sport not only because of the threat they pose to athletes' health but also because of the threat they pose to athletes' displaying the relevant types of sporting excellence.